Optically controlled properties of nanoparticles stabilised by photochromic difurylethene‐base diarylethenes: Optisch kontrollierbare Eigenschaften photochromer Difurylethen‐basierter Diarylethene. Issue 2 (16th February 2016) - Snegir, S.; Mukha, I.; Sysoiev, D.; Lacaze, E.; Huhn, T.; Pluchery, O.
Abstract : In this manuscript we describe the development of a hybrid organometallic coating to be used on glass surface. This coating consists of gold nanoparticles covered by difurylethene‐based diarylethene (DAE) photochromic molecules which are investigated covalently bound on glass slides. Diarylethene being attached to the gold nanoparticles by thiol groups formed mainly disordered monolayer on the Au Np surface. Nanoparticles bearing the open‐ring form of DAE showing an up to 6 % increased intensity of the absorption band maximum at λ = 520 nm compared to unmodified nanoparticles. This value was even increased to 22 % when the nanoparticles ware covered with a monolayer of the closed ring DAE, revealing a strong variation of the local refractive index of gold nanoparticles. Moreover, besides modification of the gold nanoparticles refractive index, the DAEs interacted most probably with the local surface plasmon resonance excitation. This was evident by a blue shift of the absorbance band of the long wave absorbance of the nanoparticles instead of the expected red shift. Simultaneously with the observed blue shift a strong increase of intensity of the visible light absorption was observed. The obtained results are discussed in view of the calculated values of visible‐light absorbance of gold nanoparticles chemically attached to glass slides.